Kotak Safety Box Bagasse Sebagai Tempat Sampah Limbah Medis Dari Bahan Dasar Limbah Ampas Tebu - Dona Martilova; Novia Nurrahmawati; Neneng Lisma Sari; Nia Listari (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
In the Riau region, especially in the city of Pekanbaru, there are many sellers of sugarcane ice drinks who produce a lot of wasted bagasse waste. The processing of bagasse waste from these sellers is not optimal so there is still a lot of rubbish strewn around the road which causes environmental pollution. Therefore, to optimize waste cleaning, apart from throwing it away, we took the initiative to use the bagasse waste into safety boxes. In general, sugar cane bagasse has fiber properties that are almost the same as those of broadleaf wood fiber. The aim of this service is to utilize waste that still has the potential to be reprocessed into high-value goods. This service method is divided into 3 stages, namely the survey stage, production stage and marketing stage. The result of this service was that a 5ml safety baggage box was formed with a selling price of IDR 35,000.00 per box. The bagasse safety box is a unique product on the market because it uses sugarcane bagasse waste and uses an environmentally friendly concept.